Fildelning – hot eller möjlighet? - om medhjälpsansvar kan aktualiseras för en abonnent som tillåter olaglig fildelning från dennes internetanslutning. - Hakobjan,Maria (2019)
This essay analyze if a subscriber of an Internet connection can be sentenced for complicity when a copyright infringement is identified on the subscribers internet connection. Filesharing occurs in a larg extent in the society and there is no clear supervision in the matter. It is therefore a great significant to investigate this question. The essay explains the copyright and the criminal responsibility for complicity and the summary is that there is a possibility for an individual subscriber to be held accounted for complicity, if that individual active provided his internet connection to another, and had knowledge about the illegal infringements on the his internet connection, and he chooses not to act. In any other case it is considered to be too extend the complicity responsibility, witch is problematic due to swedish legality principle.
Keywords: Straffrätt; fildelning